1988
DOI: 10.1177/0148607188012005509
|View full text |Cite
|
Sign up to set email alerts
|

Use of Hydrochloric Acid to Clear Obstructed Central Venous Catheters

Abstract: Central venous catheters are being used with increasing frequency to administer drugs, and as a result, catheter obstruction caused by precipitation of poorly soluble fluid components has become a common problem. We report our first experience using 0.1 N hydrochloric acid to restore patency to central venous catheters obstructed from insolubility-induced precipitation. Precipitation was caused by drug as well as calcium and phosphorus incompatibilities. The initial use of urokinase in two cases was unsuccessf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…Although the rate of occlusion, at 16%, was comparable to other studies (9% [2], 7% [3], 40% [4], 11% [5]) our rate of salvage, once blocked, was low. Other centres have shown that an occluded TIVAD may be saved by injecting urokinase [4] or hydrochloric acid 0.1 M [7] through it, with a potential success rate of up to 96% [4]. We did not find this possible, owing to rupture or disconnection of the catheter.…”
Section: Discussionmentioning
confidence: 59%
“…Although the rate of occlusion, at 16%, was comparable to other studies (9% [2], 7% [3], 40% [4], 11% [5]) our rate of salvage, once blocked, was low. Other centres have shown that an occluded TIVAD may be saved by injecting urokinase [4] or hydrochloric acid 0.1 M [7] through it, with a potential success rate of up to 96% [4]. We did not find this possible, owing to rupture or disconnection of the catheter.…”
Section: Discussionmentioning
confidence: 59%
“…This small amount is unlikely to cause a metabolic acidosis. 36 Breaux et al 37 Of further interest is a fascinating study from Canada. In a retrospective review, 42 pediatric oncology patients at the Children's Hospital at Westmead, Canada, received IV antibiotics and 2-M HCl between 1994 and 2000.…”
Section: Nonthrombotic Catheter Occlusionmentioning
confidence: 99%
“…Acidic drugs such as vancomycin and etoposide can be cleared using 0.1-N hydrochloric acid (0.1-N HCl) 39 ; 0.1-N HCl was also used to clear a catheter occlusion secondary to the sequential administration of amikacin, piperacillin, vancomycin, and heparin. 36 When the occlusion is suspected to be the result of basic medications (eg, ticarcillin, oxacillin, heparin, phenytoin, imipenem) it can be cleared with sodium bicarbonate (1 mL of 1 mEq/mL) 40 or 0.1-N NaOH. 42 Shulman et al 36…”
Section: Nonthrombotic Catheter Occlusionmentioning
confidence: 99%
“…Appropriate treatment depends on the suspected cause of the occlusion. Obstructions thought to be caused by precipitation of low-pH medications or calcium phosphate crystals that become insoluble in basic solutions can be treated with 0.1% hydrochloric acid 2628,31,32. Although our center still uses this method, the practice has been discontinued in some institutions because of concern about damaging the wall of the catheter.…”
Section: Introductionmentioning
confidence: 99%